2015
DOI: 10.4238/2015.may.4.12
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of idiopathic membranous nephropathy in young adults

Abstract: ABSTRACT. The aim of this study was to understand the clinicopathological features and prognosis of idiopathic membranous nephropathy (IMN) in youth. A retrospective analysis of the clinicopathological features and prognoses of pathologically confirmed IMN in 21 patients aged 15-30 years was performed. IMN was mainly characterized as nephrotic syndrome (NS), with stage I as the main pathological stage, and associated with hyperplasia of the glomerular mesangial cells and ground substance. High-intensity immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In pediatric cases of MN, however, hematuria is more common and has been reported in up to 69% of patients [14]. Among those of Asian ancestry, the prevalence of hematuria has been reported to be as high as 92% and 100% in cohorts of MN cases from Japan and China, and gross hematuria was found in 30% and 28%, respectively [20,21]. …”
Section: Clinical Manifestations and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…In pediatric cases of MN, however, hematuria is more common and has been reported in up to 69% of patients [14]. Among those of Asian ancestry, the prevalence of hematuria has been reported to be as high as 92% and 100% in cohorts of MN cases from Japan and China, and gross hematuria was found in 30% and 28%, respectively [20,21]. …”
Section: Clinical Manifestations and Prognosismentioning
confidence: 99%
“…Although reported rates in children are variable, hypertension appears to be less common in the pediatric MN population [7,14,21]. Thromboembolism is a significant life-threatening complication of nephrotic syndrome and thromboembolic events are more common in MN than in other causes of the nephrotic syndrome.…”
Section: Clinical Manifestations and Prognosismentioning
confidence: 99%
“…10 In previous studies, some typical clinical manifestations have been identified in patients with MN, such as NS, edema, hypertension, renal failure, and microscopic hematuria. 11 According to the guidelines of pathology, MN cases can be divided into four pathological stages (stages I, II, III, and IV). 12,13 Renal dysfunction can usually be detected in patients who have had MN for 5-10 years and pathological stage III or IV.…”
mentioning
confidence: 99%
“…IMN occurs typically in middle-aged adults, with the main clinical manifestation being the nephrotic syndrome (10). Treatment of IMN using immunosuppressants is controversial, because there are two conflicting possibilities: 1) progression to renal failure and end-stage renal disease, 2) spontaneous remission, which is more common than expected (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…On the 5th day, renal biopsy was performed. Histopathology showed typical stage II MN including diffuse thickening of the basement membrane and a large number of electron-condensing substances on the subepithelium (10). An immunofluorescence examination showed granular IgG and C3 deposition on the capillary loops.…”
Section: Case Reportmentioning
confidence: 99%